Role of High-resolution computed tomography (HRCT) in the detection of temporal bone pathology with Histopathological correlation (Anwer Khan Modern Medical College Journal, 2022)
Background & objective: Pathology of ear is the third most common reason of visiting an Otorhinolaryngologist. Imaging plays an important role, especially in complicated and recurrent conditions and influence the treatment.Because of complicated anatomy radiographic assessment of temporal bone is difficult. An HRCT scan is useful for detail anatomical evaluation, assessment of different pathology, determining the extension and site of cholesteatoma and its sac, assessing the ossicles, evaluating the facial nerve, tegmen and sinus plate, and determining dural, sigmoid sinus, and jugular bulb positions. It is excellent in accurate assessment of pathology prior to surgical exploration regarding location, extent and complication of the disease.Method: A cross sectional study was carried out in the Department of Radiology and Imaging, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka in collaboration with the Department of Pathology and Department of ENT of BSMMU and ENT and Head Neck Cancer Hospital, Dhaka, during December 2016 to November 2017, to evaluate the extent of middle ear infections, benign and neoplastic conditions involving temporal bone according to compartment involved.For this purpose, a total of 65 patients having symptoms related to temporal bone pathology was included in this study. HRCT was done for every patient. HRCT findings and diagnoses of the pathologies were then correlated with the histopathological reports. Consecutive type of purposive sampling method was used in this study.Result: There was mild male preponderance.Majority (96.9%) patients had soft tissue lesion evaluated .by high-resolution computed tomography (HRCT) findings. Predominant findings are inflammatory, 52(80.0%) of the patients , followed by 11(16.9%) benign and 2(3.1%) malignant lesions. In histopathological evaluation 53(81.5%) of the patients had Inflammatory condition, followed by 11 (16.9%) benign and 1(1.5%) malignant lesions. The validity test of CT scan in the evaluation for benign lesion had sensitivity 81.8%, specificity 96.3%, accuracy 93.8% and positive predictive values 81.8% and negative predictive value 96.3%. CT in the evaluation for malignant lesion had sensitivity 100.0%, specificity 96.9%, accuracy 96.9%, positive predictive values 33.3% and negative predictive values 100.0%. CT in the evaluation for inflammatory lesion had sensitivity 94.3%, specificity 83.3%, accuracy 92.3%, positive predictive values 96.2% and negative predictive values 76.9%.Conclusion: In this study we found significant correlation between the histopathological diagnosis and HTCT of temporal bone pathology, where the validity tests are higher in evaluation of malignant lesion followed by inflammatory and benign. So it can be concluded that the high-resolution computed tomography is a useful diagnostic modality which enables characterization of a wide range of temporal bone pathology and can be used as a reliable tool.AKMMC J 2021; 12(2): 91-97